Heterogeneity of Macrophages in Atherosclerosis - Stremmel, Christopher; Stark, Konstantin; Schulz, Christian (Thrombosis and Haemostasis, 2019)
Atherosclerosis is a prevalent inflammatory condition and a frequent cause of morbidity and mortality worldwide. Macrophages are among the key immune cells driving lesion formation in the arterial wall. They have therefore evolved as potential targets for therapeutic strategies. Understanding of the different macrophage phenotypes and functions seems to be of pivotal importance for the development of treatments to target these immune cells. This review highlights the complexity of the mononuclear phagocyte system and summarizes important features of macrophage biology contributing to atherosclerosis.
Keywords: atherosclerosis; macrophage; monocyte; inflammation; therapy